Development of novel real-time PCR methodology for quantification of COL11A1 mRNA variants and evaluation in breast cancer tissue specimens. Issue 1 (December 2015) - Karaglani, Makrina; Toumpoulis, Ioannis; Goutas, Nikolaos; Poumpouridou, Nikoleta; Vlachodimitropoulos, Dimitrios; Vasilaros, Spyridon; Rizos, Ioannis; Kroupis, Christos
Abstract Background Collagen XI is a key structural component of the extracellular matrix and consists of three alpha chains. One of these chains, the α1 (XI), is encoded by theCOL11A1 gene and is transcribed to four different variants at least (A, B, C and E) that differ in the propensity to N-terminal domain proteolysis and potentially in the way the extracellular matrix is arranged. This could affect the ability of tumor cells to invade the remodeled stroma and metastasize. No study in the literature has so far investigated the expression of these four variants in breast cancer nor does a method for their accurate quantitative detection exist. Methods We developed a conventional PCR for the general detection of the generalCOL11A1 transcript and real-time qPCR methodologies with dual hybridization probes in the LightCycler platform for the quantitative determination of the variants. Data from 90 breast cancer tissues with known histopathological features were collected. Results The generalCOL11A1 transcript was detected in all samples. The developed methodologies for each variant were rapid as well as reproducible, sensitive and specific. Variant A was detected in 30 samples (33 %) and variant E in 62 samples (69 %). Variants B and C were not detected at all. A statistically significant correlation was observed between the presence of variant E and lymph nodes involvement (p  = 0.037) and metastasis (p  = 0.041). Conclusions With the newly developed tools, the possibility of inclusion ofCOL11A1 variants as prognostic biomarkers in emerging multiparameter technologies examining tissue RNA expression should be further explored.